Flipped Learning In Listening Class: Best Practice Approaches and Implementation - Leni Irianti; Fera Sulastri (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This recent study analyzes the feasibility of the best practices concerning how flipped classroom is implemented in listening class, either online or offline. Recently, one of the digital literacy models is Mobile Assisted Language Learning (MALL) based teaching technique is well known as flipped learning classroom. It believes as a branch of blended-learning. The emergence of this new model is the vice versa from the conventional teaching process. In Flipped Classroom, the course is divided into two parts, inside and outside classroom. This model has been widely adopted in many levels of education field all over the world. Therefore, this study tries to implement flipped classroom model in university level. The course subject of this study is listening comprehension. English listening comprehension in university has its own issue. Listening has become one of the most significant concerns in teaching English as a foreign language. It was figured out that there were some problems occur in listening class. Thus, this recent study is aimed at giving precise insight toward the flipped classroom model in listening class. The research method used is case study research design. The population is the students at one of the private universities and one state university in East Priangan Indonesia. The sample is 21 students at the third semester of English Department. The questionnaires and interview were used to verify the data. The result of this study is to give precise insight implementing flipped classroom model in online and offline. It also explained the successful running of flipped classroom under the MALL